Envolvimento dos alunos em atividades de modelagem matemática: Relação com o saber e possibilidades de ação - Da Silva Campos, Ilaine; De Loiola Araújo, Jussara [UNESP] (FapUNIFESP (SciELO), 2015)
In this paper, we present the results of an investigation that sought to understand the involvement of two students, members of a group, in a mathematical modelling activity, based on the relationship that they have established with mathematical knowledge. Supported by Bernard Charlot's theoretical framework - the relationship to knowledge - and using a qualitative approach, we analysed three episodes in which the group is developing a modelling project. Besides the episodes, interviews promoted a deep understanding of aspects related to the students' involvement. Our analysis gave rise to the construction of the concept of possibilities of action. As a result, we noticed that the relationship of each student to mathematical knowledge plays a decisive role in his/her possibilities of action and that students' involvement in modelling activities can be understood not only as the actions effectively performed by them, but also as the possibilities of action that they glimpse.
Students' involvement in mathematical modelling activities: Relationship to knowledge and possibilities of action
Keywords: Mathematical modelling; Mathematics education; Mathematization; Qualitative approach; Students' practice